Principal of KMI (Kulliyatul Mu’allimin Al-Islamiyah) Efforts to Upgrade Teacher’s Professionalism - Agus Yasin; Bella Dwi Regista Syukur; Citra Eka Wulandari; Aldania Febri Almiranda Zafirah (AL-ASASIYYA: Journal Of Basic Education, 2021)
This study aims to understand and reveal the efforts of the Principal of KMI (Kulliyatul Mu’allimin Al-Islamiyah) to upgrade teachers’ professionalism. For this goal, this research used field research, with a qualitative research approach. The object field for this research is Darussalam Gontor for Girls first College, Sambirejo, Mantingan, Ngawi, East Java, Indonesia. The research methodology consists of data reduction, display data, and concluding data. With all of this process of research found that the efforts of the Principal of  KMI to upgrade teacher’s professionalism competence contain 5 point’s: (1) encouraging teachers active involvement in academic and non-academic activities; (2) holding Kamisan routines meeting to evaluate learning activities; (3) improving teachers understanding about special subject material within ta’hil programs; (4) direct observation on learning process through learning supervision in the classroom; and (5) requiring teachers to make teaching preparations before entering the learning process at the classroom.